Tinjauan Yuridis Pembuktian Sederhana Sebagai Syarat Penundaan Kewajiban Pembayaran Utang (Studi Putusan PKPU No. 288/Pdt-Sus/2023/PN.Niaga.Jkt.Pst) - Juda Kahulta Sembiring; Radian Syam (Neolectura, 2026)
Postponement of Debt Payment Obligations (PKPU) is one way for debtors to avoid bankruptcy. The main purpose of Postponement of Debt Payment Obligations is to reach an agreement between the debtor and creditor, which, if approved, will be ratified by the Commercial Court. The problems in this research are how to submit a request for Postponement of Debt Payment Obligations (PKPU) according to Law Number 37 of 2004, how PKPU applicants fulfill the simple evidentiary requirements when submitting a PKPU request, and the legal considerations of the panel of judges in applying simple evidentiary requirements in the decision of PKPU case No. 288/Pdt-Sus/2023/PN.Niaga.Jkt.Pst. The research method used is library research, namely by conducting research on various reading sources, namely books, legal magazines, opinions of scholars, laws and regulations, and also lecture materials. Data analysis used in this study uses a qualitative analysis approach. The research approach uses a conceptual approach and a case approach. The results of the study are that Law Number 37 of 2004 regulates the mechanism for submitting a Suspension of Debt Payment Obligations (PKPU) involving debtors and creditors, by giving creditors the opportunity to submit a PKPU in addition to the debtor. Concrete cases such as the PKPU Case Study of PKPU Decision No. 288/Pdt-Sus/2023/PN.Niaga.Jkt.Pst reflect the complexity of business and legal relations in Indonesia, where conflicts in business agreements can trigger lawsuits and efforts to find a peaceful solution through the PKPU process.